TRANSLATION TECHNIQUES USED IN AUDIO-VISUAL TRANSLATION: SUBTITLING AND DUBBING - ORIGINAL SOUNDTRACK MOVIE IN FROZEN 2: INTO THE UNKNOWN - Lubis, Putri; Thabran, Yulhenli; Habizar (JELT (Jambi-English Language Teaching), 2024)
The aims of this research were to determine the types and the most dominant translation technique used to translate the source language into the target language in subtitling and dubbing in OST Frozen 2: Into the Unknown. This research uses qualitative research design. The data was derived from the lyrics of Disneyâ€™s â€œInto the Unknownâ€ song. The subtitling version was taken from the Frozen 2 movie. While the dubbing version comes from one of Indonesiaâ€™s television networks, GTV. The researcher conducted this research by collecting, classifying, analyzing, and concluding the data. The results of this research showed that ten translation techniques by Molina and Albir (2002) were found in the subtitling version, are Adaptation (1 data), Amplification/Addition (1 data), Calque (4 data), Compensation (1 data), Established Equivalent (2 data), Linguistic Amplification (2 data), Literal Translation (7 data), Modulation (2 data), Reduction (9 data), and Transposition (3 data). Reduction technique is the most dominant translation technique in the subtitling version. It has the highest data frequency, 9 data. However, ten translation techniques by Molina and Albir (2002) were found in the dubbing version, those are Adaptation (1 data), Amplification/Addition (1 data), Calque (1 data), Compensation (1 data), Established Equivalent (1 data), Linguistic Amplification (2 data), Linguistic Compression (7 data), Literal Translation (1 data), Modulation (3 data), and Reduction (10 data). Reduction technique is the most dominant translation technique in the dubbing version. It has the highest data frequency, 10 data.